2009
DOI: 10.1007/s11557-008-0582-0
|View full text |Cite
|
Sign up to set email alerts
|

New species of rust fungi (Uredinales) from South Africa and new observations on known species

Abstract: Four new species and a new variety of rust fungi (Uredinales) are described from South Africa: Puccinia montis-venenosi on Galium spurium ssp. africanum and G. tomentosum, P. naufraga on Helichrysum sp., Uredo fynbosense on Phylica oleifolia and Ph. buxifolia, Uromyces eclipsis on Zygophyllum morgsana, and Puccinia lycii var. bizonata on Lycium sp. Puccinia austro-africana is proposed as a new combination for P. tetragoniae var. austro-africana on Tetragonia. New observations are presented about already known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Firstly, a list is outdated after any taxonomic change or new discovery. For example, since Berndt (2008b) compiled the latest list of rust fungi for southern Africa, at least four new species were described (Berndt 2008a;Maier et al 2015;Martin et al 2017;Wood et al 2014), several new species reported (Berndt 2009;McTaggart et al 2015b;Mostert et al 2008;Mostert et al 2010;Roux et al 2013) and names changed (Beenken and Wood 2015;Berndt 2008a). Secondly, lists often do not provide information on morphology or how to identify taxa.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, a list is outdated after any taxonomic change or new discovery. For example, since Berndt (2008b) compiled the latest list of rust fungi for southern Africa, at least four new species were described (Berndt 2008a;Maier et al 2015;Martin et al 2017;Wood et al 2014), several new species reported (Berndt 2009;McTaggart et al 2015b;Mostert et al 2008;Mostert et al 2010;Roux et al 2013) and names changed (Beenken and Wood 2015;Berndt 2008a). Secondly, lists often do not provide information on morphology or how to identify taxa.…”
Section: Introductionmentioning
confidence: 99%